Sharia Fintech Research Trends Bibliometric Analysis, Scientific Publications in 2017-2025 - Maimuna, Maimuna; Setiawan, Firman (Electronic Journal of Education, Social Economics and Technology, 2025)
This study uses a bibliometric analysis of the publication trends of Islamic fintech from 2017 to 2025.  The purpose of this study is to observe the development of publications on sharia fintech and find future research avenues and opportunities. The results of the data obtained were analyzed using quantitative-descriptive methods through the Publish or Perish application, Microsoft Excel, and VOSviewer after being collected from Google Scholar using the keyword "sharia fintech". The results show that the number of publications increased from 2017 to reaching its peak in 2023, but experienced a drastic decline in 2024 and 2025. Through bibliometric analysis, topic mapping found five main clusters: Islamic banking services, the development of sharia-based digital crowdfunding, post-COVID-19 digital transformation, and the integration or incorporation of sharia principles and technologies such as blockchain and artificial intelligence (AI). The results of the visualization of trends regarding sharia fintech have undergone a change from the pandemic to the development of halal technology and sharia business models. This research makes an important contribution in enriching our understanding of the direction and gaps of research that are still open in the future. This study enhances our understanding of the progress of Islamic fintech and encourages collaboration between academics, regulators, and industry players to create innovative, inclusive digital solutions to develop Islamic fintech that is in accordance with Islamic principles and meets the needs of modern society.